Characterization of 16-kDa major allergen with α-amylase inhibitor domain in tartary buckwheat seeds. (February 2018) - Zheng, Bei; Zhang, Haina; Wang, Lei; Guo, Yanfei; Chen, Peng
Highlights: Established the separation and identification methods of 16-kDa allergen from tartary buckwheat seeds. The recombinant Fag t 2 was expressed in Pichia pastori and purified by immobilized metal affinity chromatography. Fag t 2 was a major allergen with the activity of IgE binding and pepsin resistance, along with the thermal stability. Fag t 2 contained an AAI domain near the end of C-terminal. Abstract: Tartary buckwheat ( Fagopyrum tataricum, TB) is an important functional food containing proteins with balanced amino acid composition and more flavonoids than common buckwheat ( Fagopyrum esculentum, CB). Buckwheat contains highly potent allergens that trigger an allergic reaction via an IgE mediated response. In this work, the full-length cDNA encoding Fag t 2 from tartary buckwheat seeds was cloned by screening the cDNA library of seed-filling period. The recombinant Fag t 2 (rFag t 2) expressed in Pichia pastoris SMD1168H was purified by purified by immobilized metal affinity chromatography. It demonstrated that Fag t 2 was a major allergen in tartary buckwheat with the activity of IgE binding and pepsin resistance, along with the thermal stability. The identification of natural Fag t 2 (n Fag t 2) confirmed that the Fag t 2 protein belongs to the 2S albumin family, only existing in embryo. Most interesting, we discovered that Fag t 2 had a α-amylase inhibitor domain near the end of C-terminal. The possible activity of α-amylase inhibitor of Fag t 2 will be detected in subsequent studies.